SME Finance - Ayyagari, Meghana (World Bank, Washington, DC, 2017)
This paper takes stock of the empirical evidence on the financing challenges faced by small and medium enterprises, especially in developing countries. The paper first discusses the institutional constraints that impede access to finance, including the lack of reliable credit information, lack of suitable collateral, and weak legal institutions. It next highlights firm heterogeneity among small and medium enterprises in accessing finance. The focus is on various policies and reforms that have been shown to be effective in improving access to credit for small and medium enterprises. The paper concludes by highlighting areas where new research could be effective.